IMPLEMENTATION OF INFORMATION TECHNOLOGY IN FINANCIAL SYSTEM AT UNIVERSITY X - Retta, Intan Ilsa Alma; Hastuti, Theresia Dwi (Finance and Banking Program, Accounting Department, Politeknik Negeri Semarang, 2023)
The rapid development of technology requires organizations to keep up with innovation in order to achieve competitive advantages. University X is a university that is beginning to prepare for this wave of change by implementing a system in the financial transaction process. This study aims to analyze the application of information technology in the financial system at University X. The data collection approach used in this study is the interview method. It is a qualitative descriptive study that uses primary data. The respondents in this study were those who were directly involved in the transition process from manual work before 2011 to using the new IFS system in 2022, including the Deputy Chancellor for Finance, Head of Finance, Staff of the Salary Section of the Finance Section, Staff of the Bookkeeping Section of the Finance Section, and System Staff in the HR Section. The results of the analysis can be concluded: before 2011, a manual system was implemented, then from 2011 to 2016, an intranet system was implemented; from 2016 to 2018, the development was intranet system A; from 2019 to 2020, the K-system; and from 2022 until now, IFS. However, before 2019, the payroll division was still worked out manually using simple Excel and printed payslips. From 2019 to 2020, a new system was implemented that could provide notifications of expired allowances. The findings in this study can be used to assist universities dealing with technological changes, especially in the process of implementing a new financial system so that it can be accepted by its users and, moreover, the system is actually implemented successfully in an organization.